A Survey of Multimedia-Assisted English Classroom Teaching Based on Statistical Analysis. (11th March 2022) - Wang, Hui
Abstract : With the promotion of information technology and education reform, multimedia classroom teaching, which has distinctive teaching characteristics, rich teaching resources, and vivid teaching forms, has been widely used in different classrooms, especially in English classrooms. However, there are still some problems in the application of multimedia-assisted instruction, and much work so far has focused more on language input (vocabulary, listening, and reading) of multimedia-assisted instruction, but there is limited empirical research on output (especially writing) of it. Therefore, from the perspective of statistical analysis, this empirical study investigates the effectiveness of multimedia-assisted English classroom teaching from the detailed aspects like preferred teaching activity, understanding key and difficult points, and overall performance and then formulates a multimedia writing teaching model in order to improve students' writing performance. The result shows that multimedia teaching does have superior advantages and the model enhances students' interest and scores in writing.